Photocatalytic dye decolorization under light-emitting-diode irradiation by silver halides prepared from hydrohalic acids - Pongsaton Amornpitoksuk (2020)
© 2019 IOP Publishing Ltd. Silver halides were synthesized using a precipitation reaction between silver salts and hydrohalic acids. These products were characterized by X-ray diffractometry, scanning electron microscopy, UV-vis diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy. The photocatalytic decolorization of the dye solutions under light-emitting-diode irradiation depended mainly on the surface area of the silver halide. On the first run, AgCl prepared from 5 M HCl showed the best activity for the decolorization of both methylene blue and reactive orange. After five recycling runs, however, AgBr prepared from 5 M HBr decolorized both dyes more effectively than that of AgCl prepared from 5 M HCl.